Efektivitas program E-TLE dalam penegakan hukum peraturan berlalu lintas di Kota Jambi - Amril, Nabila Munawaroh; Anderson, Irzal; Hajri, Priazki (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to determine and analyze the effectiveness of law enforcement against traffic violations with Electronic Traffic Law Enforcement (ETLE) in the Jambi City Resort Police area and the obstacles to implementing Electronic Traffic Law Enforcement (E-TLE) in enforcing traffic regulations in Jambi City. This research was conducted at Jambi Police. The approach used is a descriptive qualitative approach. The resulting data will be in the form of descriptions in the form of words and images and does not emphasize numbers. Research data was obtained by conducting interviews with police, community offenders and the general public. The informants who were used as subjects included: 3 Jambi City traffic police officers, 4 community offenders, and 4 members of the general public. The results of the research are that law enforcement against traffic violations in the city of Jambi through electronic traffic tickets or Electronic Traffic Law Enforcement (ETLE) based on Law Number 22 of 2009 concerning Road Traffic and Transportation is carried out according to the rules but is not enough to be said to be effective. Inhibiting factors in implementing the E-TLE program include: 1. Law enforcement, 2. Facilities and infrastructure factors, 3. Community factors.